A Review on Some Biochemical markers in Metabolic-Associated Fatty Liver Disease - Ashour, Sarah; Abdullah F. Yousif; Rasha. N. Aljabery (University of Thi-Qar Journal of Science, 2023)
Liver is a primary organ for lipid and glucose homeostasis and is the focus of cardio metabolic disease. The NAFLD definition combines the existence of steatosis in more than 5% of hepatocytes and metabolic risk factors, particularly obesity and T2DM, and exclusion of excessive alcohol consumption defined as ≥ 30 g per day for men and ≥ 20 g per day for women, or other chronic liver diseases In the year of 2020, it was suggested that the nomenclature of nonalcoholic fatty liver disease (NAFLD) should be updated to metabolic-associated fatty liver disease (MAFLD), Moreover, it was found that diagnosis of MAFLD should be based on the presence of metabolic dysfunction not the absence of other conditions , MAFLD can coexist with other liver diseases and a reference to alcohol should not be included in the MAFLD acronym. Biochemical parameters play a significant role in the careful diagnosis and also for the risk assessment and adopting treatment that improves clinical outcome. This article, focused on the nomenclature and diagnosis of metabolic-associated fatty liver disease which before 2020 was called non-alcoholic fatty liver disease, and explain some of the biochemical parameters in this disease.